Tradurre (il) queer: L'esempio della letteratura polacca contemporanea (TEST Ticontre. Theory Text Translation, 2020)
The article aims at examining the main issues regarding the relationship between literary translation and non-normative sexual identities. Firstly, the ongoing debate and the major methodological proposals on the subject will be presented and contextualized. Secondly, aspects regarding sociolects, lack of correspondence between linguistic systems, camp aesthetics and intertextuality will be discussed. The analysis will be performed on a selection of texts by contemporary Polish writers like Micha? Witkowski, Izabela Filipiak, Monika Mostowik and Eugeniusz Tkaczyszyn-Dycki. Lastly, translation strategies aimed at maintaining the elusive character of queer texts in the interlinguistic and intercultural transfer will be presented.
Keywords: Translation; Queer; Polish Literature